Finite Element Stress Simulation of Six-hole Tight-waist Laminated Coupling Under Different Load - Yinghao Zhao; An'gang Cao; Rupeng Zhu; Miaomiao Li (Jixie chuandong)
Laminated couplings are often subject to torque， centrifugal force， axial displacement and angular displacement during operation. The stress analysis of the laminated couplings under various loads can provide a reliable guarantee for the safe operation of the power plant. The finite element model of the six-hole tight-waist laminated coupling considering the contact between the laminated plates is established. The stress value and stress distribution characteristics of the laminated plate under the single effects of torque， centrifugal force， axial displacement and angular displacement are analyzed. And by changing the preload force of the bolts and the friction coefficient between the lamination， their influence on the stress characteristics of the coupling is studied. The results show that increasing the bolt preload and friction coefficient will cause the maximum equivalent stress value of the outermost laminate to increase under the action of torque， axial displacement and angular displacement， but it has little effect on the stress under centrifugal force.